Coffee Consumption and Kidney Function: A Mendelian Randomization Study - Kennedy, Oliver J; Pirastu, Nicola; Poole, Robin; Fallowfield, Jonathan A; Hayes, Peter C; Grzeszkowiak, Eryk J; Taal, Maarten W; Wilson, James F; Parkes, Julie; Roderick, Paul J (American journal of kidney diseases, 2020)
Chronic kidney disease (CKD) is a leading cause of morbidity and mortality worldwide, with limited strategies for prevention and treatment. Coffee is a complex mixture of chemicals, and consumption has been associated with mostly beneficial health outcomes. This work aimed to determine the impact of coffee consumption on kidney function. Genome-wide association study (GWAS) and Mendelian randomization. UK Biobank baseline data were used for a coffee consumption GWAS and included 227,666 participants. CKDGen Consortium data were used for kidney outcomes and included 133,814 participants (12,385 cases of CKD) of mostly European ancestry across various countries. Coffee consumption. Estimated glomerular filtration rate (eGFR), CKD GFR categories 3 to 5 (G3-G5; eGFR<60mL/min/1.73m ), and albuminuria. GWAS to identify single-nucleotide polymorphisms (SNPs) associated with coffee consumption in UK Biobank and use of those SNPs in Mendelian randomization analyses of coffee consumption and kidney outcomes in CKDGen. 2,126 SNPs were associated with coffee consumption (P<5×10 ), 25 of which were independent and available in CKDGen. Drinking an extra cup of coffee per day conferred a protective effect against CKD G3-G5 (OR, 0.84; 95% CI, 0.72-0.98; P=0.03) and albuminuria (OR, 0.81; 95% CI, 0.67-0.97; P=0.02). An extra cup was also associated with higher eGFR (β=0.022; P=1.6×10 ) after removal of 3 SNPs responsible for significant heterogeneity (Cochran Q P = 3.5×10 ). Assays used to measure creatinine and albumin varied between studies that contributed data and a sex-specific definition was used for albuminuria rather than KDIGO guideline recommendations. This study provides evidence of a beneficial effect of coffee on kidney function. Given widespread coffee consumption and limited interventions to prevent CKD incidence and progression, this could have significant implications for global public health in view of the increasing burden of CKD worldwide.